2011
DOI: 10.1037/a0023647
|View full text |Cite
|
Sign up to set email alerts
|

Relationship-specific identification and spontaneous relationship maintenance processes.

Abstract: Attractive alternative partners pose a relational threat to people in romantic relationships. Given that people are often limited in their time and energy, having the capacity to effortlessly respond to such relational threats is extremely useful. In 4 studies, we explored how people's identity in terms of their romantic relationship—their relationship-specific identity—affects their relationship-protective behaviors. We predicted that once a relationship becomes a part of one's sense of self, relationship mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 164 publications
1
57
0
Order By: Relevance
“…Recent research (Linardatos & Lydon, ) indicates that even those low in relational‐interdependent self‐construal might nevertheless view themselves as connected to their romantic relationship—what we refer to as relationship identification. An individual may not identify with his or her close relationships in general, but because of meaningful experiences within his or her romantic relationship, he or she may include this romantic relationship as an important part of his or her self (Overall, Fletcher, & Friesen, ).…”
Section: Relationship Identification and Commitmentmentioning
confidence: 93%
“…Recent research (Linardatos & Lydon, ) indicates that even those low in relational‐interdependent self‐construal might nevertheless view themselves as connected to their romantic relationship—what we refer to as relationship identification. An individual may not identify with his or her close relationships in general, but because of meaningful experiences within his or her romantic relationship, he or she may include this romantic relationship as an important part of his or her self (Overall, Fletcher, & Friesen, ).…”
Section: Relationship Identification and Commitmentmentioning
confidence: 93%
“…Cross‐sectional findings show that derogation of alternatives is associated with higher levels of commitment (Etcheverry et al, ), love (Gonzaga, Haselton, Smurda, Davies, & Poore, ), a stronger relational identity (Linardatos & Lydon, ), secure attachment (Overall & Sibley, ), and self‐regulation (Ritter, Karremans, & van Schie, ). Moreover, meta‐analytic findings show that perception of high‐quality alternatives (e.g., failure to derogate alternatives) robustly predicts dissolution (Le et al, ).…”
Section: Research On Relationship Maintenancementioning
confidence: 99%
“…This effect is especially pronounced for people who are strongly (vs. weakly) satisfied with or committed to their current partner (Cole, Trope, & Balcetis, 2016;Johnson & Rusbult, 1989;Lydon et al, 1999;Lydon, Fitzsimons, & Naidoo, 2003; see also Meyer, Berkman, Karremans, & Lieberman, 2011). Another series of studies has demonstrated that People as Means 9 people committed to their partner direct attention away from attractive alternatives (Linardatos & Lydon, 2011;Maner, Gailliot, & Miller, 2009).…”
Section: Principle 7 Shieldingmentioning
confidence: 99%
“…For example, a person can limit his/her appeal or attractiveness to potential partners (Forest, Krueger, & Orehek, 2017;Frankenhuis & Karremans, 2012) and can avoid opportunities to help others progress toward their goals. Preventing alternatives from seeming instrumental can be executed by devaluing alternative partners Lydon et al, 2003;Lydon et al, 1999) and by directing attention away from alternatives (Linardatos & Lydon, 2011;Maner et al, 2009). …”
Section: Relationship Maintenancementioning
confidence: 99%